PRECONCENTRATION OF LEAD(II) IONS IN AIR PARTICULATE (PM2,5) WITH ION IMPRINTED POLYMER BY USING FLOW INJECTION ANALYSIS-FLAME ATOMIC ABSORPTION SPECTROPHOTOMETRY - Ambarsari, Novita
Lead is one of the most common metal elements found in the environment. The main source of lead has historically been from motor vehicle emissions using leaded gasoline, although the use of leaded gasoline is now banned. In addition, other sources of lead in the atmosphere come from mining activities, burning wood and coal, smelting, refining metals, and burning waste. The nature of lead which cannot be degraded biologically and can accumulate in the human body, makes lead exposure can cause various health problems in humans. Monitoring of lead content in the environment needs to be carried out continuously as a way to evaluate lead pollution and estimate the impact of lead pollution in the future on human health and the environment. Determination of low levels of lead with good accuracy and high selectivity is still a challenge because the concentration of lead in the environment is quite low as well as the complexity of the matrix in environmental samples. Therefore, it is necessary to have a separation method that can be used for lead separation as well as a pre-concentration method with high selectivity that is able to analyze lead in complex environmental samples at low levels (micro). One of the most widely used separation and preconcentration methods is Solid Phase Extraction (SPE) with Ion Imprinted Polymers (IIPs) used as functional materials. IIPs used in SPE have advantages such as fast binding kinetics, can be used repeatedly, have a large adsorption capacity, and are easy to use in automating the extraction process. Selection of the right ligand/complexing agent in the synthesis of IIPs can improve the performance of IIPs with high selectivity. In this study, ion imprinted polymers for lead (Pb-IIP) were synthesized by entrapment technique involving Pb(II) ternary complex with Pyridilazo resorcinol (PAR) and 4-Vinyl Pyridine (4-VP) ligands. PAR can form complexes with Pb(II) ions and together with vinyl pyridine (VP) can form ternary complexes with Pb(II). The vinyl group on the VP will covalently bind to the polymer backbone during polymerization, while the PAR ligand will be trapped in the polymer matrix. Thus the position of the mold on the IIP can be maintained after the template is removed from the polymer. Non-Imprinted Polymer (NIP) was synthesized as a comparison with two types of NIP, with the addition of PAR ligand (NIPP) and without the addition of PAR ligand (NIP). The type of ligand used and the ability of the polymer to maintain the geometrical structure of the mold affect the adsorption ability and selectivity of IIP. Polymers with short-chain compositions can provide high rigidity. Methacrylic acid (MAA) is used as a functional monomer in the synthesis of Pb-IIP which is known to be widely used because of its ability to act as proton and hydrogen bond donors and hydrogen bond acceptors. MAA has a very reactive double bond and is soluble with monomers that are soluble in water and oil. The carboxylate group in MAA can promote the formation of polymer particles. TRIM was chosen as a crosslinker which is expected to form a polymer network that is stronger in maintaining the three-dimensional impression of the template. The performance of IIP, namely high affinity and selectivity, is determined by the interaction of the metal with the ligand and also the number of active sites formed during polymerization. Characterization of polymer materials has been carried out including physical characterization by analysis of FTIR, SEM-EDX, TGA, BET, and zeta potential. Optimization of the synthetic composition and polymerization techniques were carried out to obtain polymers with the best capacity and imprinting factor (IF). The polymer was then evaluated for retention performance by batch method and SPE column followed by the use of Pb-IIP as a sorbent in the preconcentration technique based on flow injection analysis (FIA), and its application in determining the concentration of Pb(II) in air particulate samples (PM2,5). The results of the evaluation of retention performance with the batch method resulted in a maximum adsorption capacity value of 14.3 mg/g for Pb-IIP, 12.56 mg/g, and 10.63 mg/g for NIPP and NIP. The optimum adsorption conditions were pH 6, a contact time of 120 minutes, a sorbent mass of 25 mg, adsorption kinetics following the pseudo-second-order model, and adsorption isotherms following the Langmuir model. The separation factor and selectivity of Pb-IIP to Pb(II) ions in the presence of other metal ions, namely Cu(II), Cd(II), and Zn(II) showed the highest selectivity coefficient in the quaternary solution. The adsorption-desorption cycle of the Pb-IIP sorbent in the SPE column for repeated use of more than five cycles still gives the value of % recovery > 95% and pre-concentration can be carried out up to 4 times with 3 M HNO3 as eluent and 100 mg sorbent mass. Preconcentration based on FIA-FAAS using a mini-column with a sorbent mass of 35 mg, a flow rate of 1.5 mL/min, and carrier aqua DM pH 6 using an eight-way valve system resulted in a dynamic retention capacity value of 5.20 mg/g with a concentration of Pb(II) 40 mg/L. Breakthrough volume was reached at 2.97 minutes. The analytical performance of FIA-FAAS obtained 3.09% precision, 0.9925 linearity, 5.11 g/L detection limit, 16.84 g/L quantification limit, with accuracy in the range of 90%-110% which shows the effect of the matrix in the sample does not have a significant effect on the Pb(II) analysis process. The resulting FIA performance is an enrichment factor of 23.33 times, a concentration efficiency of 11,65 per minute, and a consumptive index of 4.5 mL. The short analysis time and small volume of reagents, as well as the ease of combining with various instruments are the advantages of the FIA-FAAS technique. The application of the FIA-FAAS system with Pb-IIP sorbent for preconcentration and analysis of Pb(II) ions in particulate air (PM2.5) samples resulted in a fairly good accuracy value and the concentration of Pb(II) in PM2.5 samples used in This research is 174.29 ng/m3 and 217.86 ng/m3. This value is still below the safe threshold set by the government, which is 2000 ng/m3 for a sampling duration of 24 hours. The technique of preconcentration and separation of Pb(II) ions with the FIA-FAAS system using the synthesized Pb-IIP sorbent in this study can be used for the analysis of Pb(II) ions with trace levels in samples, especially environmental samples. The effect of the matrix that can be minimized makes this method can be used as an alternative method in the analysis of Pb(II) with trace levels using general instruments such as FAAS so that it can be carried out in many laboratories that do not yet have other instruments used in the standard method.